Constructions de la subjectivité dans la littérature érotique féminine - Swoboda, Tomasz (Romanica Silesiana)
Constructing Subjectivity in Women’s Erotic Writing The distinction between eroticism and pornography implies judgments significant for the author’s position in the literary field. Contemporary women writers, aware of the mechanisms that manage this field, enter into a complex game with the public and, above all, against sexual stereotypes. Authors like Catherine Millet, Virginie Despentes, Catherine Breillat and Nelly Arcan opt for sexual liberty and concentrate their writing on the body that becomes the main expression of woman’s subjectivity. Nevertheless, they rest imprisoned by the stereotypes they fight against, and often favour the rhetoric of opposition, well out-of-date in comparison with queer theories. Key words: pornography, eroticism, women’s writing, stereotypes, sexual liberation.